Instant Porridge Formulation Based on Cassava Flour and Tempe Flour Composite for Children - Sri Inten Utami; Made Astawan; Tjahja Muhandri (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
Improving the nutrition of affordable and economically weaning food is an effective strategy to prevent stunting in children. Cassava, as a source of carbohydrates, and tempe, as a source of protein, when processed into composite flour, have the potential to serve as key ingredients in instant weaning food. This study was conducted in two stages. The first stage involved preparing the raw materials by making composite flour. The formula optimization process was carried out using a mixed experiment optimization method and D-optimal design to identify the best formula. The formula was selected based on predetermined response measurements, including maximum protein content, viscosity within the desired range, rehydration power within range, and appropriate density. In the second stage, the selected formula was evaluated through analysis of its physicochemical properties, sensory attributes, and in vitro protein and starch quality. The optimization results indicated that the best cassava-tempe porridge (CTP) formula consisted of 24.58% tempe flour and 43.42% cassava flour (based on the total material). The nutritional composition (moisture, ash, fat, protein, and carbohydrate content) and microbiological count (total plate count) were as follows: 3.27%, 3.39%, 8.29%, 18.74%, 66.31%, and 7.5×101 CFU/g, respectively. In terms of physical properties, CTP exhibited a viscosity of 2306.67 cP, rehydration power of 3.67 mL/g, density of 0.45 g/mL, and a color (L*) of 83.06. The starch and protein digestibility were 74.60% and 81.25%, respectively. The optimized CTP formula met the quality standards outlined in SNI 7111:2005 for instant powdered complementary foods for infants. The sensory evaluation revealed a hedonic score for the attributes of color (6.31), aroma (6.24), viscosity (6.46), taste (6.06), and overall acceptability (6.06), indicating that the product was well-liked.